(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The study develops a new antenna design of circular coplanar waveguide (CPW) and simulates using an electromagnetic solver for wireless band applications. The developed antenna design comprises the layer of CPW in conjunction with the rhombus ring and circular patch.